Interacting dark energy in a closed universe. Issue 1 (4th January 2021) - Di Valentino, Eleonora; Melchiorri, Alessandro; Mena, Olga; Pan, Supriya; Yang, Weiqiang
ABSTRACT: Recent measurements of the Cosmic Microwave Anisotropies power spectra measured by the Planck satellite show a preference for a closed universe at more than $99 {{\ \rm per\ cent}}$ confidence level (CL). Such a scenario is however in disagreement with several low redshift observables, including luminosity distances of Type Ia supernovae. Here we show that interacting dark energy (IDE) models can ease the discrepancies between Planck and supernovae Ia data in a closed Universe, leading to a preference for both a coupling and a curvature different from zero above the 99 per cent CL. Therefore IDE cosmologies remain as very appealing scenarios, as they can provide the solution to a number of observational tensions in different fiducial cosmologies. The results presented here strongly favour broader analyses of cosmological data, and suggest that relaxing the usual flatness and vacuum energy assumptions can lead to a much better agreement among theory and observations.